2008
DOI: 10.1007/s10459-008-9123-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes stories: use of patient narratives of diabetes to teach patient-centered care

Abstract: A critical component to instituting compassionate, patient-centered diabetes care is the training of health care providers. Our institution developed the Family Centered Experience (FCE), a comprehensive 2-year preclinical program based on longitudinal conversations with patients about living with chronic illness. The goal of the FCE is to explore the experience of illness from the patient's perspective and ultimately to incorporate this perspective in clinical practice. In this qualitative study, we wished to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 13 publications
1
83
0
Order By: Relevance
“…Thus, students introduced identified life-world problems to GPs as part of an overall assessment of the patient's current state of disease thereby enabling an increased understanding on the part of the GP of the everyday life of the patient. The potential of home medication interviews to explore life-world problems has also been demonstrated by medical students [30].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Thus, students introduced identified life-world problems to GPs as part of an overall assessment of the patient's current state of disease thereby enabling an increased understanding on the part of the GP of the everyday life of the patient. The potential of home medication interviews to explore life-world problems has also been demonstrated by medical students [30].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Research data was obtained with the use of focused interview by Merton and Kendall (Cohen and Manion, 1994) at two different times (before and after the intervention), and the patient's answers were content-analyzed using Grounded Theory methodology (Kumagai et al, 2009;Lundin, 2008;Strauss and Corbin, 1998). Grounded theory seeks to derive thematic categories from initial data.…”
Section: Case Studymentioning
confidence: 99%
“…Narrative reasoning helps practitioners to be more capable of recognizing, interpreting and being moved to action by the individual stories of illness (Charon, 2004(Charon, , 2006, which impact their approach to reasoning and practice, as well as the outcomes of that practice (Hall et al, 2010;Kumagai, Murphy, and Ross, 2009;Resnik and Jensen, 2003). Accordingly, research in this area has associated these capabilities with expert practitioners (Edwards, Jones, Carr, and Jensen, 2004;Jensen, Gwyer, Shepard, and Hack, 2000;May, Greasley, Reeve, and Withers, 2008;Resnik and Jensen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several different educational strategies have been proposed to develop students' clinical reasoning capabilities, ranging from empirico-analytical approaches associated with the development of hypotheticodedutive reasoning, to interpretative approaches focused on the development of narrative reasoning capabilities Parry, 2008;Ross and Haidet, 2011;Swisher et al, 2012). With regard to narrative reasoning, research has suggested that the use of narratives increases students' understanding about the patient illness experience and promotes the implementation of patient-centered practice (Hurwitz, Greenhalgh, and Skultans, 2004;Kumagai, 2008;Kumagai, Murphy, and Ross, 2009;Lévesque, Hovey, and Bedos, 2013).…”
Section: Introductionmentioning
confidence: 99%